Analysis of the spatial distribution of metabolites in Aloe vera leaves by mass spectrometry imaging and UHPLC-UHRMS - Sumi Krupa; Tomasz Ruman; Wiktoria Szuberla; Joanna Nizioł (Scientific Reports)
Abstract This study presents an investigation of the chemical composition of Aloe vera leaf tissue with a focus on the spatial distribution of compounds. The composition was studied using two mass spectrometry imaging techniques: silver-109 nanoparticles assisted laser desorption/ionization mass spectrometry imaging (109AgNPs-LDI-MSI) and laser ablation-remote atmospheric pressure photoionization/chemical ionization mass spectrometry imaging (LARAPPI/CI-MSI) and the identification was aided by ultra-high-performance liquid chromatography and ultra-high-resolution mass spectrometry (UHPLC-UHRMS) analysis. The results showed an abundance of phenolic compounds with antioxidant, antimicrobial, and anti-inflammatory properties, making it a beneficial food additive and food packaging material. Analysis of the results of mass spectrometry imaging provided information about the potential changes in metabolic pathway expression in different regions of the leaf.